2016
DOI: 10.1186/s12936-015-1076-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of malaria in the Taabo health and demographic surveillance system, south-central Côte d’Ivoire

Abstract: Background A deep understanding of the local epidemiology of malaria is essential for the design and implementation of setting-specific control and elimination efforts. In Côte d’Ivoire, new initiatives are underway to reduce the burden of malaria, which requires high-quality longitudinal data. The epidemiology of malaria was studied in the Taabo health and demographic surveillance system (HDSS) in south-central Côte d’Ivoire and implications for control are discussed.MethodsTwo cross-sectional surveys were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
(40 reference statements)
1
25
2
1
Order By: Relevance
“…Many previous studies have found that males are more likely to have Plasmodium infections than females [14, 3133]. In this study, men working in the forests had much higher infection rates.…”
Section: Discussionmentioning
confidence: 44%
“…Many previous studies have found that males are more likely to have Plasmodium infections than females [14, 3133]. In this study, men working in the forests had much higher infection rates.…”
Section: Discussionmentioning
confidence: 44%
“…A study carried out in villages from the central region of Côte d'Ivoire led to similar results (Ouattara et al, 2014). Another study carried out in the central south region of the country in 2010 and 2011 presented a prevalence of 46 and 56 % respectively (Bassa et al, 2016), indicating that infection prevalence is function of period, epidemiological facies and vegetation that promote and maintain anopheles pressure (Raso et al, 2012). The correlation between malaria infection and factors such as the use of treated insecticide nets, education level, age and residential environment demonstrate the role of these factors in malaria epidemiology.…”
Section: Discussionmentioning
confidence: 66%
“…But the agreement observed was slightly higher compared to that reported by Kilonzo et al [ 30 ] (kappa: 0.354) in Tanzania. A recent study in Yemen by Alareqi et al [ 31 ] also reported a kappa of 0.379 for both febrile and afebrile participants and a higher weighted kappa of 0.638 among only febrile patients. Thus RDT could be used for malaria diagnosis in settings where microscopy is not available [ 32 ].…”
Section: Discussionmentioning
confidence: 97%